Evaluation of threonine inclusion in a diet on productivity and carcass characteristics of indigenous Boschveld chickens - Sekgotodi, Tebogo Mack (My University, 2023)
Protein ingredients are the most expensive inputs in poultry production even though not included in large quantities compared to energy ingredients. The study aimed to evaluate dietary threonine levels for optimal production and carcass characteristics of indigenous Boschveld chickens. Two experiments were conducted to determine the effect of dietary threonine levels on the productivity and carcass characteristics of indigenous Boschveld chickens. The first part of the study was to determine the effect of threonine inclusion level in a diet on feed intake, feed conversion ratio, body weight gain and gut organ measurements of unsexed indigenous Boschveld chickens aged 1 to 49 days. A total of 200-day-old chicks, weighing 30 ± 5g per bird, were randomly allocated to 5 dietary treatment levels in a completely randomized design (CRD), replicated four times with 10 chicks per replicate. The experimental diets were isocaloric and isonitrogenous, and were made to fulfil the necessary nutritional standards, but with different threonine inclusion levels of 4, 7.5, 8, 8.5, or 9 g per kg DM of diet. Data were analysed using Statistical Analysis System version 9.4 and it was subjected to one-way analysis of variance (ANOVA). A quadratic equation was used to determine dietary threonine levels for optimal duodenum pH and duodenum weights of unsexed indigenous Boschveld chickens aged 49 days. Threonine inclusion levels had an effect (p<0.05) on feed intake, body weight gain, and feed conversion ratio of unsexed indigenous Boschveld chickens aged 1-49 days. Threonine inclusion levels had no effect (p>0.05) on crop, gizzard, ileum, jejunum, caeca, large intestine pH values and caeca lengths of unsexed indigenous Boschveld chickens aged 49 days. However, threonine inclusion levels had effect (p<0.05) on duodenum pH, GIT, duodenum, large intestine lengths, crop, gizzard, ileum jejunum, and caeca weights of unsexed indigenous Boschveld chickens aged 49 days. Feed conversion ratio, duodenum pH values and duodenum weights of unsexed indigenous Boschveld chickens were optimized at dietary threonine level of 12.00, 0.70 and 8.00 g/kg DM, respectively. The second part of the study was to determine the effect of threonine level in a diet on carcass characteristics and quality of male indigenous Boschveld chickens aged 50 to 91 days. A total of 75 male chickens weighing 600 ± 10g were used in a completely randomized design having 5 treatment groups, replicated three times, with five chickens per replicate. The experimental diets were formulated to be isocaloric and isonitrogenous and meet the nutritional requirements, but with different threonine inclusion levels of 4, 7.5, 8, 8.5, or 9 g per kg DM of feed. Data were analysed using Statistical Analysis System version 9.4 and was subjected to one-way ANOVA. A quadratic equation was used to determine dietary threonine levels for optimal large intestine lengths, crop, and jejunum weights of male indigenous Boschveld chickens aged 91 days. Threonine inclusion levels had an effect (p<0.05) on feed intake, body weight gain (BWG), and feed conversion ratio (FCR) of male indigenous Boschveld chickens aged 50 to 91 days. The BWG, FCR, crop, jejunum, and large intestine lengths of male indigenous Boschveld chickens were optimized at dietary threonine levels of 6.12, 6.87, 5.95, 5.66, and 6.08 g/kg respectively. Threonine inclusion levels had no effect (p>0.05) on crop, gizzard, ileum, jejunum, duodenum, caeca, large intestine pH values, GIT, caeca lengths, large intestine weights, juiciness, flavour, overall acceptability, and cooking loss of indigenous Boschveld chickens aged 91 days. However, dietary threonine inclusion levels had an effect (p<0.05) on large intestine lengths, crop, and jejunum weights, carcass, thigh, drumstick, breast, and abdominal fats weights, and tenderness of male indigenous Boschveld chickens aged 91 days. It is concluded that dietary threonine levels used in this study affected the production performance of indigenous Boschveld chickens aged 1-49 more than indigenous Boschveld chickens aged 50-91 days. However, production variables were optimized at different dietary threonine levels. This has implication on diet formulation for the chickens. Thus, there is a need for further studies on the subject to ascertain the present findings
Thesis (M.Sc. (Animal Production)) -- University of Limpopo, 2023
Keywords: Threonine; Indigenous Boschveld chickens; feed intake; Body weight gain; Feed conversion ratio; Carcass characteristics; Gut organ; Chicken breed; Weight gain; Poultry; Chickens -- Feeding and feeds; Proteins in animal nutrition